Analysis of the promoter region of the gene encoding NAD-dependent methylenetetrahydrofolate dehydrogenase-methenyltetrahydrofolate cyclohydrolase. - Bélanger, C (1991)
Sequence analysis of the 5'-flanking region of the gene encoding NAD-dependent methylenetetrahydrofolate dehydrogenase-methenyltetrahydrofolate cyclohydrolase (NMDMC) revealed several putative cis-regulatory elements. To delineate the function of these regulatory elements, various deletion mutants of the 5'-flanking region were connected to the reporter gene chloramphenicol acetyltransferase (CAT) and promoter activity was measured in transient transfection assays. Transfection experiments performed with the sequence extending from -508 to +59 produced a high-level transient expression of the CAT gene in BALB/c 3T3-SV-T2 and NIH 3T3 cells. Removal of the sequence from +16 to +59 which includes the second transcription start point at +43, a TATA-like box and 5'-untranslated sequences abolished the promoter activity. Deletion analysis of 5'-upstream sequences revealed that the region from positions -55 to +59 is sufficient to mediate a high CAT activity comparable to the level obtained with the construct -508/+59. Within this region are found a CAAT box, a TATA-like box and two putative GC boxes. A functional analysis of the promoter showed that the sequence from -55 to +59 is sufficient to respond to stimulation by serum.